Examining provision and sufficiency of testing accommodations for English learners. Issue 1 (6th February 2021) - Roschmann, Sarina; Witmer, Sara E.; Volker, Martin A.
Abstract: Accommodations are commonly provided to address language-related barriers students may experience during testing. Research on the validity of scores from accommodated test administrations remains somewhat inconclusive. The current study investigated item response patterns to understand whether accommodations, as used in practice among English learners (ELs) in the United States, allow for comparable measurement between ELs and non-ELs. Results indicated that although significant differences are evident in overall test scores for ELs and non-ELs, only minimal measurement concerns were evident. Very few items displayed moderate or large differential item functioning (DIF); no tests showed small, medium, or large differential test functioning. The current study adds to existing literature on measurement comparability and accommodation research on ELs; implications for practice are provided.